The influence of hydrostatic pressure on DADP-type antiferroelectrics - Levitskii, R.R.; Moina, A.P. (Condensed Matter Physics, 1998)
We study the effects of hydrostatic pressures on deuterated ND₄D₂PO₄ type antiferroelectric crystals. Within the four-particle cluster approximation the free energy of the crystals is calculated, and an equation for the transition temperature and explicit expressions for static dielectric permittivities of the crystals are derived. Model pressure dependences of the effective dipole moments of unit cells are proposed. Some peculiarities of the dipole moment formation in these hydrogen bonded crystals are elucidated. In particular, we show the importance of mutual polarization of the dipole moments. The theory parameters providing a satisfactory description of the experimental data for pressure dependences of transition temperature and dielectric characteristics of the considered crystals are found.